Citric acid cross-linking of heat-set whey protein hydrogel influences its textural attributes and caffeine uptake and release behaviour. (October 2016) - Zand-Rajabi, Hadiseh; Madadlou, Ashkan
Abstract: Heat-induced whey protein gels were either pre-loaded with caffeine, then cross-linked with citric acid, or vice versa. Based on the results of Fourier transform infrared spectroscopy, the pre-loading then cross-linking procedure caused less cross-linkage formation than the cross-linking then caffeine loading (post-loaded) procedure. The latter also resulted in a firmer gel. The caffeine-to-protein ratio was approximately 8.5 μg mg −1 in the non-cross-linked hydrogel; those of the caffeine-loaded then cross-linked and the cross-linked then caffeine-loaded hydrogels were 4.5 and 2.9 μg mg −1, respectively. Cross-linking decreased swelling of the freeze-dried gels upon subsequent rehydration. It also influenced the extent of caffeine release from the protein hydrogel. Pre-loaded and post-loaded samples retained ∼78% and ∼88%, respectively, of the entrapped caffeine after immersion in water for 4 h; the non-cross-linked gel retained <55% of the initially loaded caffeine. Caffeine loading decreased gel water-holding capacity; subsequent citric acid cross-linking increased water-holding capacity.